(untitled) (Journal of Medical & Health Sciences Review, 2025)
Class II maloclussion is the most prevalent in orthodontic patients. During camolflauge treatment of this maloclussionnasolabial angel increases inevitably for which a threshold value needs to be defined. Objective: The objective of this study was to calculate the mean score for the modified profile of a woman of class II div 1, by digitally simulating a rise in nasolabial angle from the initial image. Methods: This cross-sectional study was undertaken at Puniab Dental Hospital/de’ Montmorency College of Dentistry from July 15 to December 01, 2024. A profile picture and lateral cephalometric radiograph of a female with an untreated skeletal Class 2 Division I relationship, a normal mandibular plane angle and normal face height were used. The NLA of the subject’s profile image was adjusted to 104.9±4º using Adobe Photoshop CS2. The base image was then digitally changed to produce additional profile photographs, imitating increase in nasolabial angle by 2.0, 4.0, and 6.0 standard deviations (corresponding images called C, B, and A in the questionnaire). Results: The mean age of lay persons was 29.14±5.41 years, minimum age was 18 and maximum age was 41 years. The gender of 90(58.1%) were males and 65(41.9%) were females. Mean attractiveness of facial profile was evaluated by calculating mean attractiveness as the lay people rank the images from 1 to 5. Mean attractiveness score was 4.74±0.44 for image B followed by 4.54±0.50 for image A, 4.37±0.50 for image C and 3.27±0.45 for base image. Conclusions: According to the study, both the nontreated and profile with biggest nasolabial angle (NLA) had the least pleasing appearance. To achieve an aesthetic profile at the end of treatment while treating a class II DIV 1 patient the nasolabial angle should not exceed 121°.